Escala de comportamento dos pais durante as refeições: comparação das respostas entre pais e filhos em uma população de adolescentes com excesso de peso - Volpe, Carolina Bertagnoli [UNIFESP] (2017)
The objective of this study was to compare the responses of parents and children to the Portuguese version of the Parent Mealtime Action Scale (PMAS) and to evaluate the associations between the reported behaviors. To compare the responses, a cross-sectional study was carried out with 72 patients from the Obesity Outpatient Clinic of the Discipline of Nutrology of the Department of Pediatrics of the Federal University of São Paulo (Unifesp) from 10 to 19 years and 11 months and their parents or guardians. First, the parents were interviewed and instructed to respond to the frequency (never, sometimes or always) with which they performed each of the PMAS behaviors. Then the teenagers answered the same questions. The general linear model (GLM) showed effect of the respondents and the interaction between respondents and sex. Finally, we also found an effect of triple interaction (sex x respondents x categorized age). The internal consistency of the PMAS scale was greater in relation to parents' responses than to their children's. This is probably due to the fact that the scale has been developed and validated to evaluate the pattern of parents' responses to their children's eating behavior. In addition, we note that parental strategies are already known, but the effectiveness of these strategies is not recognized by the children. Based on the analysis of the intra-class correlation between the original domains of the PMAS scale for parents and children, very low values ​​are observed (CCI: 0.130 - 0.578), showing that the factorial structure of PMAS can be considered only to evaluate the behavior of the parents and does not have adequate accuracy to evaluate the behavior of the children in relation to their own eating behavior.